The Concept of Morality in the Qur'an and Hadith: The Foundation for Building the Islamic Generation - Moh Solehuddin; Muhammad Arsyad; Hadi Widodo; Rahima Sikumbang (PT. Anagata Sembagi Education, 2025)
This research aims to examine the concept of morality in the perspective of the Qur'an and Hadith and its urgency as a foundation in forming an Islamic generation in the modern era. Morality in Islam is not only understood as manners or social behavior, but is an integral part of faith and the main pillar in building civilization. Using the library research method, this study analyzes the verses of the Qur'an and the hadiths of the Prophet Muhammad related to noble morals, as well as explores strategies for instilling these values in the lives of the younger generation. The results of the study show that the moral values of the Qur'ani and the Prophet such as honesty, trust, patience, and justice are a solid foundation in the formation of individual Muslim character. However, the challenges of globalization, moral crises, and foreign cultural influences require a strategic and collaborative approach, both through family, school, community education, and the creative use of digital media. This study recommends the need to revitalize moral education systematically and sustainably in order to produce a generation that is not only intelligent, but also noble.